Eliciting risk preferences experimentally versus using a general risk question: Does financial literacy bridge the gap? - Calvin Mudzingiri; Ur Koumba (Risks, 2021)
The study investigates the stability of financial risk preference choices elicited from subjects by way of two methods, namely: experimentally elicited incentivized revealed risk preferences (IRRP) and (self-reported) perceived willingness to take a financial risk (PWTFR). The research further examines whether financial literacy (a human capital aspect) helps in reducing the gap between IRRP and PWTFR choices made by subjects. A total of 193 university students (where 53% were female) participated in the study. The subjects completed IRRP choices from four multiple price list (MPL) risk preference tasks and a financial literacy questionnaire. There is a tendency to anchor at extremes of risk-seeking behavior when subjects self-report their PWTFR choices. A paired t-test analysis of the two methods shows that the average responses from the two methods are significantly different. A random effect (RE) panel regression shows that an increase in financial literacy narrows the gap between IRRP and PWTFR choices. The study's findings show that responses by subjects from a PWTFR general risk question (GRQ) and IRRP experiment are unstable and inconsistent. What people say in a survey does not always translate into what they do when faced with a risk preference choice dilemma. Financial literacy helps individuals to predict their risk attitudes more precisely.
Keywords: A13; C91; I30; 330; financial literacy; general risk question; incentivized revealed risk preferences; perceived financial risk; risk tolerance gap; theory comparison approach